The first fossil Dufoureillini (Hemiptera: Heteroptera: Anthocoridae: Lyctocorinae) from the Eocene Baltic amber - Popov, Yuri A.; Herczek, Aleksander; Broòek, Jola (Zootaxa, 2011)
The paper presents description of new anthocorid taxa from the inclusions in the Upper Eocene Baltic amber: Xyloesteles parvulus gen.nov and sp. nov. and Xyloesteles kerneggeriorum sp. nov. They are described and illustrated here. These fossil flower bugs of the family Anthocoridae (s.l.) belong to the tribe Dufouriellini Van Duzee (Lyctocorinae) are reported for the first time.